2005
DOI: 10.1590/s0101-81752005000400058
|View full text |Cite
|
Sign up to set email alerts
|

Predação de morcegos por Chrotopterus auritus (Peters) (Mammalia, Chiroptera) no pantanal de Mato Grosso do Sul, Brasil

Abstract: Foi registrada a predação de Carollia perspiscillata (Linnaeus, 1758) e Peropterix macrotis (Wagner, 1843) por Chrotopterus autitus (Peters, 1856) em uma caverna na morraria do Urucum em Corumbá, centro-oeste do Brasil. Os fragmentos de asas e um crânio encontrados sob o local de pouso de C. auritus junto às fezes, após comparados com material de coleção, mostraram que este morcego alimenta-se oportunamente de outras espécies de morcegos ocupantes do mesmo abrigo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
5
0
5
Order By: Relevance
“…Previous reports indicate that C . auritus is most likely an opportunistic hunter that feeds mostly on small vertebrates such as rodents, bats, birds, and occasionally insects [19,20,2226]. Prey commonly taken by C .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that C . auritus is most likely an opportunistic hunter that feeds mostly on small vertebrates such as rodents, bats, birds, and occasionally insects [19,20,2226]. Prey commonly taken by C .…”
Section: Discussionmentioning
confidence: 99%
“…Acosta y Lara (1951) reported predation on Glossophaga soricina (Pallas, 1766); Bordignon 2005 reported the predation of Carollia perspicillata (Linnaeus, 1758) and Peropterix macrotis (Wagner, 1843) in a cave. Nogueira et al 2006 also reported predation of C. perspicillata , which was found partially eaten in a mist net.…”
Section: Introductionmentioning
confidence: 99%
“…Small bats throughout the world fall prey mainly to vertebrates, such as mammals, birds, snakes, amphibians, and pet animals (BORDIGNON, 2005;KAŇUCH;BALÁŽ, 2005;LEFEVRE, 2005;ESBERARD et al, 2006;ESBERARD;VRCIBRADIC, 2007;CASTRO et al, 2011;KHLAFALLA;IUDICA, 2012;ANCILLOTTO et al, 2013;GARRIDO-GARCÍA et al, 2013), however they are also attacked by invertebrates such as large arthropods (MOLINARI et al, 2005;NYFFELER;KNÖRNSCHILD, 2013).…”
mentioning
confidence: 99%